2020
DOI: 10.2500/aap.2020.41.190021
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of plasma-derived C1-inhibitor concentrate for treatment of patients with hereditary angioedema

Abstract: Background: Replacement therapy with plasma-derived C1-inhibitor (C1-INH) has been used for decades to treat patients with hereditary angioedema (HAE) with C1-INH deficiency. Objective: This article reviewed the rationale for using C1-INH replacement therapy in patients with HAE and the process of manufacturing plasma-derived C1-INH. Methods: The manufacture of C1-INH is an involved and carefully monitored process that includes screening and selection of prospective donors, the collection of source plasma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Abbreviations: CPK, creatine phosphokinase; pdC1INH, purified nanofiltered plasma-derived human C1 esterase inhibitor concentrate; rhC1INH, recombinant human C1 esterase inhibitor a The risk of transmission of infections has been reduced by the selection of donors, testing of plasma donations for possible viral contaminants, the methods introduced in manufacturing to inactivate and/or remove viruses and other adventitious agents that might be present in the serum mixture, and regular pharmacovigilance [112]. No cases have been reported to date with currently marketed pdC1INH products [1,37].…”
Section: Prolongation Of Partial Thromboplastin Time Lanadelumab Locmentioning
confidence: 99%
“…Abbreviations: CPK, creatine phosphokinase; pdC1INH, purified nanofiltered plasma-derived human C1 esterase inhibitor concentrate; rhC1INH, recombinant human C1 esterase inhibitor a The risk of transmission of infections has been reduced by the selection of donors, testing of plasma donations for possible viral contaminants, the methods introduced in manufacturing to inactivate and/or remove viruses and other adventitious agents that might be present in the serum mixture, and regular pharmacovigilance [112]. No cases have been reported to date with currently marketed pdC1INH products [1,37].…”
Section: Prolongation Of Partial Thromboplastin Time Lanadelumab Locmentioning
confidence: 99%
“…Individuals with malfunction of C1‐INH may experience angioedema attacks. C1‐INH functionally suppresses autoactivation of factor XII and inhibits the conversion of prekallikrein to kallikrein 23 . C1‐INH is capable of inhibiting activation of C1r and C1s, and the cleavage of two important components of complement system C2 and C4 24 .…”
Section: Complement System At a Glancementioning
confidence: 99%
“…C1‐INH is capable of inhibiting activation of C1r and C1s, and the cleavage of two important components of complement system C2 and C4 24 . Moreover, C1‐INH has a regulatory role in the coagulation system through inhibition of factor XI 23 . One of the soluble complement inhibitor molecules which acts at the level of C3 convertases is C4b‐binding protein (C4BP) 25 .…”
Section: Complement System At a Glancementioning
confidence: 99%
“…Berinert and Cinryze are concentrated C1-INH collected from healthy blood donors. The mechanism of action of these molecules is the regulation of kallikrein and factor XII activity and the reduction of bradykinin production (29). Bork et al showed that the mean time of angioedema reversal in 18 HAE patients was 42.2 minutes (22).…”
mentioning
confidence: 99%